Shelf life of kenaf (Hibiscus cannabinus L.) seed stored under humid tropical conditions - Adebisi, M.A; Esuruoso, O.A.; Adetumbi, J.A; Abdul-Rafiu, A.M.; Kehinde, T.O.; Ajani, O.O.; Agboola, D.A. (Plant Breeding and Seed Science, 2012)
Successful crop production depends initially on the availability of high-quality seed. Seed viability and vigour of four kenaf varieties during storage were investigated. Seeds of each variety were packed inside thick polythene bags and kept in Seed Stores under ambient conditions in two storage locations (Federal University of Agriculture, Abeokuta (FUNAAB) (29.8°C, 59.10 RH%) and Institute of Agricultural Research and Train- ing, Ibadan (27.5°C, 64.68 RH%) for 240 days (8 months). Seeds were sampled during storage at 0, 60, 120, 180 and 240 days and tested for seed viability and seedling vigour index. Data collected on seed viability and seedling vigour were analyzed using ANOVA, mean separation using Duncan Multiple Range Test at 5% probability level and PROBIT analysis. The results showed differential responses in the two quality traits due to differences in storage location and varieties. Ibadan storage location provided more favourable conditions for higher seed quality compared to Abeokuta location while Ifeken 400 and Tianung had the best storage potential. The study showed that under ambient humid tropical conditions, storage period should not exceed 180 days (6 months) in order to maintain higher physiological quality with little or no cost. The PROBIT result revealed that the highest seed shelf life (longevity) of kenaf seeds of 8 to 9 months was derived for seeds of Ifeken 400 and Tianung stored in Ibadan and Abeokuta. The shortest shelf life of 6 months was esti- mated for Ifeken 100 stored in both locations.